2002
DOI: 10.1002/dc.10111
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of galectin‐3 and CD26/DPPIV as preoperative diagnostic markers for thyroid nodules

Abstract: The aim of this study was to search for diagnostic markers that could correctly identify thyroid nodular lesions requiring urgent surgical treatment. We investigated whether galectin-3 and dipeptidyl peptidase IV (CD26/DPPIV) could be potential markers for improving the diagnostic accuracy of conventional cytology. Seventy-nine patients with histologically proven thyroid diseases were analyzed. The immunocytochemical staining results showed galectin-3 expression in neoplastic cells of all 37 papillary carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 19 publications
1
30
0
2
Order By: Relevance
“…Among them are dipeptidylpeptidase 4 (DPP4; refs. [19][20][21][22], a-1 antitrypsin (SERPINA1; ref. 23), galectin 3 (LGALS3; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Among them are dipeptidylpeptidase 4 (DPP4; refs. [19][20][21][22], a-1 antitrypsin (SERPINA1; ref. 23), galectin 3 (LGALS3; ref.…”
Section: Discussionmentioning
confidence: 99%
“…HBME1, CK19, CD26/DPPIV, TPO and c-met have also been reported to be useful markers for improving the preoperative characterisation of thyroid nodules (De Micco et al, 1994Ruco et al, 2001;Aratake et al, 2002;Rosai, 2003;Maruta et al, 2004;Mechanick, 2004;Weber et al, 2004;Papotti et al, 2005;Prasad et al, 2005;Saggiorato et al, 2005;de Matos et al, 2005). Among the aforementioned molecules, TPO is the largest preoperatively investigated tumour marker with a high overall accuracy (De Micco et al, 1994Christensen et al, 2000;Weber et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, RT-PCR analysis demonstrated overexpression of Gal-3 in all six PTC and three FTC cases evaluated, whereas Gal-3 mRNA expression was either undetectable or identified at low levels in two of three FA cases and in all four normal thyroid tissue specimens. 53 Despite this early promise, a number of less convincing studies have followed. Martins et al found that while Gal-3 mRNA expression was higher in PTC and FTC than in benign thyroid lesions, Gal-3 transcripts were also present in FA and multinodular goiter cases.…”
Section: Reverse Transcriptase-polymerase Chain Reaction Studies Of Gmentioning
confidence: 99%